Peran Koperasi Sekolah dalam Membentuk Pola Pikir Kewirausahaan Siswa: Studi Fenomenologi di SMK Budhi Warman II Jakarta Timur - Faried, Ade Achmad; Intan, Lusi Reni; Raharjo, Didik Sapto; Hidayat, Arif (CV ODIS, 2025)
This study aims to explore the role of school cooperatives in shaping students' entrepreneurial mindset through a phenomenological approach. The research was conducted at SMA Budhi Warman II East Jakarta, with main subjects being students actively involved in school cooperative activities. Data collection methods included observation, in-depth interviews, and documentation. Data were analyzed using descriptive qualitative analysis with an inductive approach. The results showed that the school cooperative plays a significant role in building awareness, attitudes, and entrepreneurial skills among students such as initiative, responsibility, independence, and teamwork. Moreover, through direct practice in managing business within the cooperative, students can better understand real business concepts and develop their entrepreneurial mindset. These findings provide important contributions to schools and policymakers in designing effective entrepreneurship development strategies